(3OQI GdZhGU hcfR GdGNJUGU aj Yde GdNhGUs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s ((3CNeje(B- (3GdUYjO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi fhQ bdhH ChdjGFg HPcQg GdeUhf hHYO aEf GdEfSGf NRGfI GdehGgH GPG cGf HgG LOjQ hgPg ebOeI jdRe eYQaJgG def CQGO GdgLhe Ydi HYV gPg GdGbaGd s
(3BNQgG (B:s
(3aGYde Cf LedI eG MUQg GdeJCNQhf ef CbdGe GdeJbOejf hGdCNQjf GKfGf hSHYhf bdekG hgj LedI eG JbOe s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs